Introduction to Statistical Methods for Analyzing Large Data Sets: Gene-Set Enrichment Analysis - Clark, Neil R. (2011)
This Teaching Resource provides lecture notes, slides, and a problem set for a series of lectures introducing the mathematical concepts behind gene-set enrichment analysis (GSEA) and were part of a course entitled “Systems Biology: Biomedical Modeling.” GSEA is a statistical functional enrichment analysis commonly applied to identify enrichment of biological functional categories in sets of ranked differentially expressed genes from genome-wide mRNA expression data sets.